Penguatan dan Pengembangan Pendidikan Islam melalui Pendekatan Multidisipliner, Interdisipliner, dan Transdisipliner - Rahman, Fadli; Ma'ruf, Hidayat (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
Education is a basic human need. In practice, the implementation of education itself still leaves problems that have not yet been fully resolved. The problem in question is the dichotomization of education. Starting from the phenomenon of scientific dichotomization which then resulted in the emergence of the duality of the education system in Indonesia, namely Islamic religious education and science education, to separating religious and scientific awareness, the multidisciplinary, interdisciplinary and transdisciplinary approach is seen as the right approach to be used and developed by Islamic Religious College (PTKI) as the basis of Islamic higher education in integrating the duality of education. In addition, multidisciplinary, interdisciplinary, and transdisciplinary approaches have indeed become contemporary demands in an effort to answer or overcome increasingly complex humanitarian problems. In other words, the production of knowledge through the provision of education must contribute significantly to human life itself without being trapped or confined to a rigid and dichotomous way of thinking.